ELECTRONIC COMMERCE AND ELECTRONIC AGREEMENTS - Djurabayeva Aziza Sadikovna (Western European Studies, 2025)
This article deals with the concept of electronic commerce and electronic agreements, as well as their legal regulation in the Republic of Uzbekistan. E-commerce is widespread in cyberspace and is widely used by individuals and legal entities. E-commerce has its advantages and disadvantages; this article will analyse them and disclose their content. The statistics given in this article will specify the details of buying and selling in online marketplaces. Methods and stages of concluding electronic contracts will be presented. Entering into electronic contracts is a modern way of drafting and signing contracts. This article will compare paper and electronic contracts
Keywords: Cyber Law; electronic trading platforms; electronic commerce